Pulmonary tuberculosis and multidrug-resistant Mycobacterium tuberculosis in northwestern Ethiopia: a hospital-based cross-sectional study among presumptive pulmonary tuberculosis patients - Wubu, Birhanu; Jemal, Mohabaw; Million, Yihenew; Gizachew, Mucheye (Frontiers in Medicine, 2023)
Introduction: Border areas are important sites for disseminating Mycobacterium tuberculosis among individuals living in such areas. This study examined patients with suspected pulmonary tuberculosis (PTB) visiting the Abrihajira and Metema hospitals in northwest Ethiopia to investigate the prevalence of rifampicin resistant Mycobacterium tuberculosis (RR-MTB), multidrug-resistant Mycobacterium tuberculosis (MDR-MTB), and risk factors related to Mycobacterium tuberculosis infection. Methods: A hospital-based cross-sectional study was conducted from February to August 2021 among 314 PTB presumptive patients. Xpert MTB/RIF and Line probe assays (LPA) were used to process sputum samples. Data were imported into the Epi-Data 3.1 program and exported to Statistical Package for The Social Sciences (SPSS) version 20.0 (SPSS, Chicago, IL, USA) to conduct the analysis. A logistic regression analysis was used to investigate the relationship between the dependent and independent variables. A p-value of < 0.05 denoted statistical significance.Results: Of the total (314) PTB presumptive patients who participated in this study, 178 (56.69%) were males, and 165 (52.5%) were from 25 -50 years old with a median age of 35.00 (interquartile: 25-45 years). Among all patients, 12.7% had PTB by Gene Xpert, and 7/314 (2.23 %) were resistant to rifampicin. Among patients enrolled, 4/314(1.27%) had MDR-MTB (resistant to RIF and INH) by LPA. Regarding the risk factors assessed, primary level of education, sputum production, night sweating, respiratory disorder, contact history of TB, history of MDR-MTB infection, history of alcohol use, and cigarette smoking showed statistical significance with the prevalence of PTB (p < 0.05).Discussion: This study observed a high prevalence of PTB, RR-MTB, and MDR-MTB compared with many other previous studies conducted in Ethiopia. Among the assessed risk factors which could be associated with the prevalence of PTB, eight were statistically significant. This prevalence, resistance, and statistically significant variables are the evidence to which more emphasis should be given to the country's border areas.